Objek Kajian Islam (Akidah, Syariah, Akhlaq) - Yazidul Bushtomi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
The objects of Islamic study are: 1. Akidah, based on the Big Indonesian Dictionary, creed is a basic belief, a basic belief. The word aqidah, when viewed from Arabic, comes from the word